THE CHALLENGES OF MIGRANTS: WOMEN AS BEAST OF BURDENIN OUR TODAYS WORLD - Sandra, IKENYEI N.; Eseoghene, EFEBEH Vincent (International Journal of Psychosocial Rehabilitation, 2020)
One of the challenges of migrants is securing permanent residency. Illegal migrants are worst hit by the problem of residency permit-green papers. Women especially the elderly areused as a springboard to secure green cards. Vulnerable personalities who need a solution to their needs meet themselves but the unfortunate gender becomes beast of burden. Exploiting/benefiting someone’s vulnerability is a problem that is trivialized today. Although many researchers have detailed the problems of detention and deportation of illegal migrants, few have explored the problem of women as arbiter to secure permanent stay and then dumped thereafter. Thus, the study explored the challenges of migrant and women as a beast of burden. Explanation of the operative variables is anchored on firo, functionalist, Conflict and exchange theory. The research setting was selected communities in Edo and Delta, Nigeria. The research was exploratory. Method of data collection was through a questionnaire, key informant and in-depth interview. Data were content analyzed and through simple percentage with the use of statistical package for the social sciences (SPSS version 15). Responses revealed that marriage of convenience exists in the west and women are mostly the beast of burden.